2013
DOI: 10.1120/jacmp.v14i4.4065
|View full text |Cite
|
Sign up to set email alerts
|

Lung SBRT: dosimetric and delivery comparison of RapidArc, TomoTherapy, and IMRT

Abstract: This study seeks to compare fixed‐field intensity‐modulated radiation therapy (FF IMRT), RapidArc (RA), and helical tomotherapy (HT) to discover the optimal treatment modality to deliver SBRT to the peripheral lung. Eight patients with peripheral primary lung cancer were reviewed. Plans were prescribed a dose of 48 Gy and optimized similarly with heterogeneity corrections. Plan quality was assessed using conformality index (CI100%), homogeneity index (HI), the ratio of the 50% isodose volume to PTV (R50%) to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 25 publications
5
43
0
1
Order By: Relevance
“…The use of non-coplanar angles minimises the overlap between fields, spreading the intermediate doses in the cranial-caudal direction with resultant increased intermediate-dose conformity. Our findings are similar to a previous study published by Weyh et al [22], which reported coplanar VMAT/IMRT as having inferior dosimetry to helical tomotherapy in terms of conformity.…”
Section: Discussionsupporting
confidence: 94%
“…The use of non-coplanar angles minimises the overlap between fields, spreading the intermediate doses in the cranial-caudal direction with resultant increased intermediate-dose conformity. Our findings are similar to a previous study published by Weyh et al [22], which reported coplanar VMAT/IMRT as having inferior dosimetry to helical tomotherapy in terms of conformity.…”
Section: Discussionsupporting
confidence: 94%
“…Several other studies have investigated the role of different IMRT treatment techniques in the treatment of early stage NSCLC with SABR to reduce lung toxicities (27,28) . Kannarunimit et al (27) compared three SABR treatment techniques, robotic surgery, RA, and HT plan, for treatment of central lung with SABR.…”
Section: Discussionmentioning
confidence: 99%
“…Weyh et al (28) compared RA, HT, and fixed beam for SABR treatment to lesions in the peripheral lung to conclude RA and fixed beam plans were equivalent, but the reduction in treatment time with RA makes them more preferable. This study has supported their work and furthermore, our results demonstrate a decrease in all normal lung DVH parameters in RA and SA, albeit not significant.…”
Section: Discussionmentioning
confidence: 99%
“…8,10,11 Of the groups who investigated the dose to the heart, four demonstrated an advantage with IMRT 8-10,12 and two did not find any benefit. 10,14,[32][33][34][35] For example, Ong et al 13 showed an 8-minute time reduction if VMAT was used compared to IMRT. 8,10,13,14,30 Table 3 compares different IMRT planning techniques.…”
Section: Dose Distributions With Imrt Compared To Conventional 3dcrtmentioning
confidence: 99%
“…When spinal cord dose was examined, five out of six groups found a significant advantage with IMRT. Weyh et al 35 compared tomotherapy, IMRT, and VMAT and reported a significant treatment time benefit using VMAT (6.5 minutes) compared to the other two techniques (IMRT: 11.1 minutes, tomotherapy: 15.9 minutes). Apart from treatment time, there is no clear benefit for one technique above the others.…”
Section: Dose Distributions With Imrt Compared To Conventional 3dcrtmentioning
confidence: 99%